Issues for consideration at the WHO Executive Board - Hani Serag (Social Medicine Publication Group, 2024)
The People's Health Movement (PHM) has created a WHO Watch "directed to changing the patterns of global decision making and implementation in matters which affect the global health crisis." The need for such a Watch has been heightened by moves within the WHO to create an additional governing structure "that will bring together Member States, global health funds, development banks, partnerships, nongovernmental organizations, civil society organizations, and the private sector to address issues critical to global health." The private sector (which in practical terms means agribusiness, big pharma, and the interests of the medical-industrial complex) already has vast influence over health policy and it is entirely unclear why they need yet one more forum. We present here comments by the PHM on the agenda prepared by the WHO Executive Board prior to the World Health Assembly held in January 2011. They provides some ideas for an alternative health agenda.